2017
DOI: 10.3389/fpls.2017.01143
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus licheniformis SA03 Confers Increased Saline–Alkaline Tolerance in Chrysanthemum Plants by Induction of Abscisic Acid Accumulation

Abstract: Soil saline-alkalization is a major abiotic stress that leads to low iron (Fe) availability and high toxicity of sodium ions (Na+) for plants. It has recently been shown that plant growth promoting rhizobacteria (PGPR) can enhance the ability of plants to tolerate multiple abiotic stresses such as drought, salinity, and nutrient deficiency. However, the possible involvement of PGPR in improving saline–alkaline tolerance of plants and the underlying mechanisms remain largely unknown. In this study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 67 publications
3
26
0
Order By: Relevance
“…Hence, FMCH001 inoculated plants offered advantages over uninoculated control plants in regulating the level of ROS in plant cells. Similarly, Zhou et al (2017) reported enhanced activity of SOD, CAT, APX, and GPX in Chrysanthemum inoculated with B. licheniformis SA03 under saline-alkaline conditions. In addition, very recently Chiappero et al (2019) also reported similar findings, i.e., higher antioxidant capacity in inoculated plants in relation to uninoculated controls under drought stress.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, FMCH001 inoculated plants offered advantages over uninoculated control plants in regulating the level of ROS in plant cells. Similarly, Zhou et al (2017) reported enhanced activity of SOD, CAT, APX, and GPX in Chrysanthemum inoculated with B. licheniformis SA03 under saline-alkaline conditions. In addition, very recently Chiappero et al (2019) also reported similar findings, i.e., higher antioxidant capacity in inoculated plants in relation to uninoculated controls under drought stress.…”
Section: Discussionmentioning
confidence: 84%
“…Many studies have observed increased ABA accumulation in PGPR-inoculated plants under various abiotic stress conditions. Bacillus licheniformis SA03-treated Chrysanthemum morifolium in saline-alkaline conditions had nearly double the level of ABA in leaves than the control as detected by ELISA (Zhou et al 2017). Plants inoculated with SA03 and exposed to saline-alkaline stress conditions showed fewer symptoms and had higher fresh and dry shoot weights, whereas inoculated plants treated with the ABA inhibitor FLU exhibited no tolerance to the stress.…”
Section: Diverse Pgpr Molecules Elicit Plant Defensementioning
confidence: 92%
“…Most of the isolates also showed their potential in improving salt tolerance, growth, and yield of rice under salt-stress conditions. ST-PGPR strain Bacillus licheniformis SA03 isolated from Chrysanthemum plants grown in saline-alkaline soil of China conferred increased salt tolerance in Chrysanthemum (Zhou et al, 2017).…”
Section: The Diversity Of Salt-tolerant Plant Growth Promoting Rhizobmentioning
confidence: 99%